Resilience through social innovation for sustainable development (INMR - Innovation & Management Review, 2023)
Purpose: This study provides an example of the intersections between resilience and innovation within the social economy. It describes the Portuguese context, boosted by a pioneering public policy focused on building resilience through innovation. The sustainable development concept usually sets multilevel relationships among the government, social investors, and entrepreneurs. In this sense, the study explores the role of innovation in promoting resilience in initiatives and society that may lead to sustainability.Methodology: The authors collected the primary data through semi-structured interviews with social investors and an online survey with the invested or awarded entities from 2015 to 2020. The database represents 43.63% of acknowledged Portuguese social innovative initiatives, describing a complex and multilevel result. The case also provides a unique context for deepening the understanding of popular, relevant, but still underdeveloped concepts.Findings: The results highlight progress in overcoming social and economic challenges. This progress happens through innovative initiatives aiming to solve social problems that reflect collective interests. The data suggest a context dynamization due to an increase of 31.3% in new initiatives. This increase can potentially represent a consistent investment in resilience and sustainable development.Originality/value: This paper helps to contextualize and structure information for three fragmented concepts. It relies on their combination to compensate for each other frailties, assuming that innovation can be a crucial factor for boosting sustainable development, making possible the countries' resilience. It also argues that the literature state can result from a paradigm shift, and these features can favor this process toward a better world.